The Role of C-Type Lectin Receptor Signaling in the Intestinal Microbiota-Inflammation-Cancer Axis - Li, Muhan; Zhang, Runfeng; Li, Ji; Li, Jingnan (Frontiers in Immunology, 2022)
As a subset of pattern recognition receptors (PRRs), C-type lectin-like receptors (CLRs) are mainly expressed by myeloid cells as both transmembrane and soluble forms. CLRs recognize not only pathogen associated molecular patterns (PAMPs), but also damage-associated molecular patterns (DAMPs) to promote innate immune responses and affect adaptive immune responses. Upon engagement by PAMPs or DAMPs, CLR signaling initiates various biological activities in vivo, such as cytokine secretion and immune cell recruitment. Recently, several CLRs have been implicated as contributory to the pathogenesis of intestinal inflammation, which represents a prominent risk factor for colorectal cancer (CRC). CLRs function as an interface among microbiota, intestinal epithelial barrier and immune system, so we firstly discussed the relationship between dysbiosis caused by microbiota alteration and inflammatory bowel disease (IBD), then focused on the role of CLRs signaling in pathogenesis of IBD (including Mincle, Dectin-3, Dectin-1, DCIR, DC-SIGN, LOX-1 and their downstream CARD9). Given that CLRs mediate intricate inflammatory signals and inflammation plays a significant role in tumorigenesis, we finally highlight the specific effects of CLRs on CRC, especially colitis-associated cancer (CAC), hoping to open new horizons on pathogenesis and therapeutics of IBD and CAC.